In vitro Antioxidant Activities of Methanol and Aqueous Fractions of Coccinia grandis L. Voigt Stem Extract - Deshpande, S.V.; Patil, M.J.; Daswadkar, S.C. (Asian Journal of Chemistry, 2010)
The present study reports the antioxidant activities of the methanol and aqueous fractions of the stem extract of Coccinia grandis L. Voigt (Cucurbitaceae). The antioxidant activities of the fractions have been evaluated by using four in vitro assays and were compared to standard antioxidant such as butylated hydroxy anisole (BHA). Both the fractions showed effective H-donor activity, reducing power, free radical scavenging activity. The antioxidant property depends upon concentration and it is increased with increasing amount of the fractions. The free radical scavenging and antioxidant activities may be attributed to the presence of phenolic and flavonoid compounds present in the fractions. The results obtained in the present study indicate that the stem of C. grandis is a potential source of natural antioxidant.